2023
DOI: 10.1021/acs.orglett.2c04208
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Activation of C–X Bond via Carbonate-Assisted Anion−π Interactions: Applications to C–P and C–B Bond Formation

Abstract: We have presented a carbonate anion assisted photochemical protocol for the C–X bond activation. Anion−π interactions have been leveraged to generate aryl radicals from easily accessible aryl halides that are further utilized in C–P and C–B bond formation reactions with excellent reactivity and broad functional group tolerance. Spectroscopic investigations and DFT studies were conducted for mechanistic insights. This inexpensive method alleviates the use of a photocatalyst and the need of preactivation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…This transformation indicates that the reaction proceeds through the intermediate formation of aryl radicals, which are known to be readily trapped by phosphites. 48,49 Based on these data, we may suggest a mixed chain/catalytic reaction mechanism (Scheme 7). At the initiation step (PC cycle), the photocatalyst is excited by light and then is reduced to a radical anion by Sn(II) species with the simultaneous formation of SnX 3…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…This transformation indicates that the reaction proceeds through the intermediate formation of aryl radicals, which are known to be readily trapped by phosphites. 48,49 Based on these data, we may suggest a mixed chain/catalytic reaction mechanism (Scheme 7). At the initiation step (PC cycle), the photocatalyst is excited by light and then is reduced to a radical anion by Sn(II) species with the simultaneous formation of SnX 3…”
mentioning
confidence: 82%
“…We have also shown that if the reaction was carried out in the presence of 2 equiv of triethylphosphite, the stannylation reaction was inhibited and product 7 was obtained in 27% isolated yield [the naphthyl derivative was easier to isolate compared to 4-fluorophenyl analog] (Scheme , eq 4). This transformation indicates that the reaction proceeds through the intermediate formation of aryl radicals, which are known to be readily trapped by phosphites. , …”
mentioning
confidence: 99%
“…2 However, in recent years the implementation of electrocatalytic 3 and visible light-mediated 4 methods as a milder strategy for the preparation of phosphonates have been applied with success. In this field, photo-, 5 metallaphotoredox 6 and electron-donor–acceptor (EDA) methods 7 (Scheme 1A) have been employed using different aryl radical precursors, such as aryl halides, aminated arenes, or aryl sulfonates through homolytic cleavage of C(sp 2 )–heteroatom bonds. 8 In addition, two examples of light induced direct C(sp 2 )–H phosphonation have been reported in the same year.…”
mentioning
confidence: 99%
“…Overall, this method presents high functional group tolerance, and it allows to carry halides through the photochemical process, in contrast to previously reported methods. 5–7 Importantly, the thianthrene unit beyond acting as a leaving group, it is responsible to form the EDA complex with the phosphite as electron donor molecule.…”
mentioning
confidence: 99%
“…[6] It was not long before, the Lakhdar group employed the same methodology for the visible light-promoted synthesis of aryl phosphonates from diaryliodonium salts and phosphites under photoredox catalyst free conditions. [7] Similarly, the EDA complex-based strategy was used for phosphonation of aryl halides under visible [8] or UV [9] light irradiation. Unlike transition metal catalyzed reactions leading to the formation of the same products, the above-mentioned photochemical reactions feature mild conditions and a broader scope.…”
mentioning
confidence: 99%